STUDENTS’ THINKING PROCESSES IN INVERSE PROPORTION PROBLEM SOLVING - Maulidina Basalama; Nur’ain S. Patilima; Nur Elina Karim; Hikmahturrahman Hikmahturrahman; Zulfahmi Mustapa R; Suhardiman Darson Tamu; Febiyanti R. Hasan (Jurnal Education and Development, 2026)
This study describes students’ thinking processes in solving inverse proportion problems based on mathematical ability. The study employed a qualitative descriptive design involving three students categorized as having high, moderate, and low mathematical ability. Data were collected through a written inverse proportion task and task-based interviews organized according to four problem-solving stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The task asked students to determine the completion time when 20 workers who could finish a job in 30 days were increased to 50 workers. The results showed that the high-ability student recognized the inverse relation, used the constant-product model 20 × 30 = 50 × x, obtained 12 days, and verified the answer. The moderate-ability student treated the situation as direct proportion by writing 20 : 50 = 30 : x, indicating relational misconception. The low-ability student recognized the inverse relation but had difficulty with multiplication and division and did not check the answer. The findings imply that inverse proportion instruction should emphasize contextual relations, strategy selection, computational fluency, and reflective checking.